2002
DOI: 10.1016/s0092-8674(02)01074-7
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Long-Term-Memory-Related Synaptic Plasticity Involves Bidirectional Regulation of Gene Expression and Chromatin Structure

Abstract: Excitatory and inhibitory inputs converge on single neurons and are integrated into a coherent output. Although much is known about short-term integration, little is known about how neurons sum opposing signals for long-term synaptic plasticity and memory storage. In Aplysia, we find that when a sensory neuron simultaneously receives inputs from the facilitatory transmitter 5-HT at one set of synapses and the inhibitory transmitter FMRFamide at another, long-term facilitation is blocked and synapse-specific lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
410
1
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 471 publications
(434 citation statements)
references
References 22 publications
12
410
1
11
Order By: Relevance
“…They found that the consolidation of either LTP or LTD (capture of LTP or LTD) was facilitated in response to the previous induction of the late phase of the opposite form of synaptic plasticity in a separate population of synapses in the same neurons ( Figure 2L), a paradoxical phenomenon they originally referred to as "cross-tagging" (Sajikumar and Frey, 2004a), although it has been later renamed as "cross-capture" by other authors (Govindarajan et al, 2006;Morris, 2006), a term we also consider more appropriate. In this case, the situation seems to be radically different to that described in Aplysia cultured neurons, in which LTD overrides, instead of facilitate, LTF (Guan et al, 2002). The striking result in the Schaffer collateral pathway suggests that a common genetic program is activated in CA1 pyramidal neurons by both L-LTP and L-LTD triggering stimuli, whereas differential tags set at the synapses would determine whether that genetic program led to the persistence of LTD or LTP in a given synapse.…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…They found that the consolidation of either LTP or LTD (capture of LTP or LTD) was facilitated in response to the previous induction of the late phase of the opposite form of synaptic plasticity in a separate population of synapses in the same neurons ( Figure 2L), a paradoxical phenomenon they originally referred to as "cross-tagging" (Sajikumar and Frey, 2004a), although it has been later renamed as "cross-capture" by other authors (Govindarajan et al, 2006;Morris, 2006), a term we also consider more appropriate. In this case, the situation seems to be radically different to that described in Aplysia cultured neurons, in which LTD overrides, instead of facilitate, LTF (Guan et al, 2002). The striking result in the Schaffer collateral pathway suggests that a common genetic program is activated in CA1 pyramidal neurons by both L-LTP and L-LTD triggering stimuli, whereas differential tags set at the synapses would determine whether that genetic program led to the persistence of LTD or LTP in a given synapse.…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…The chromatin immunoprecipitation (ChIP) assay was performed as described by Guan et al (2002), with some modifications. The hippocampus was dissected out, fixed with 4% paraformaldehyde for 2 h, and washed in 0.125 M glycine and PBS, for 10 min each at 4°C, before it was homogenized and sonicated to obtain DNA fragments of 600 bp (average size).…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have demonstrated that chromatin modification, specifically histone hyperacetylation, plays an important role in the molecular mechanism of learning and formation of a long-term memory in Aplysia and mice [1,12,19,21]. Since associative learning is an integrated component of psychostimulant-induced sensitization [5,37], HDAC inhibitors may potentiate amphetamine-induced behavioral sensitization by enhancing associative learning and memory consolidation.…”
Section: Learning Processes Governing Amphetamine Sensitizationmentioning
confidence: 99%
“…Acetylation and deacetylation of core histone tails have been associated primarily with transcriptional activation and gene silencing, respectively [11]. Several studies suggest that dynamic histone acetylation and deacetylation processes are also active in postmitotic neurons [12,20,21,27]. Recently, it has been shown that both acute and chronic cocaine administration are able to induce specific histone modification at different gene promoters in the striatum [6,20,22].…”
Section: Introductionmentioning
confidence: 99%